EFEKTIVITAS KONSELING NARATIF UNTUK MENGATASI RENDAHNYA PSYCHOLOGICAL WELL-BEING KORBAN PERUNDUNGAN - Istiqomah, Rindang A.; Purwaningrum, Ribut; Asrowi, Asrowi (Jurnal Psikologi, 2024)
Psychological well-being is defined as the state of an individual who can have a positive attitude towards themselves and others and can make decisions according to needs by developing their potential. One strategy to overcome low psychological well-being is through narrative counseling. This study aims to examine the effectiveness of narrative counseling in overcoming the low psychological well-being of students who are victims of bullying. The approach used in this research is quantitative with a pre-experimental design. The method used was one group pretest-posttest. The research subjects were selected based on specific criteria made by the researcher. Data collection uses Ryff's Psychological Well-Being Scale which has gone through an adaptation process. The data analysis technique used in this study is the Wilcoxon Signed Rank Test to determine the difference in pretest and posttest scores. The test results are known to point to the number 0.028 <0.05. A significance value of less than 0.05 is said to have a significant difference between the pretest and posttest results. So it can be concluded that narrative counseling is effective for overcoming low psychological well-being. Suggestions that can be given to future researchers are to implement other research designs such as true experiments or develop narrative counseling media through research and development designs